A Study of Needs for Instruction and Satisfaction Towards the Master of Education Program in Educational Evaluation and Research, Ramkhamhaeng University - Masantiah, Chuthaphon; Saengngam, Juthamas; Tippayakulpairoj, Darunee (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
This research aimed to 1) study the needs of learning development of Master of Education Program in Educational Evaluation and Research (revised curriculum academic year 2022), Ramkhamhaeng University, and 2) study satisfied toward graduate’s qualification according to TQF: HEd and outcome of program for program development. There were 3 groups of participants as 75 current students, 5 graduates, and 5 employers. Research instruments were a set of questionnaires (needs, and satisfaction), and a set of memorandums (synthesis of university’s vision and mission, analysis of learning outcome, and curriculum criticism). Quantitative research data was conducted by descriptive statistics; frequency, percentage, mean, and standard deviation. Modified Priority Needs Index ( ) was used for analyzed and prioritized needs. Research finding revealed that: 1) According to, the first priority of the program was the supportive element for learning ( = 0.13) and the second was teacher’s effectiveness ( = 0.04) and 2) Graduates were highly satisfied toward graduate’s qualification according to TQF: HEd and outcome of program while employer was utterly satisfied.